Communication – Important Means of the Complaints Management - Urdziková, Jana (Vysoké učení technické v Brně, Fakulta podnikatelská, 2012)
Purpose of the article: Effective communication in an organization is one of the preconditions of its operation. The aim of the article is to point out the communication process in the complaints management, to emphasize importance of the communication in the business practice and the current state analyze of the communication in Slovak business subjects. The paper presents the partial results and conclusions of research carried out. Methodology/methods: The methodology of this study is based on the scientific methods of acquiring and processing data – observation, questionnaire, interview, qualitative methods (analysis, synthesis, induction, deduction, comparison, abstraction, etc.); quantitative methods (descriptive statistics such as frequency analysis, statistical analysis, confidence intervals) and graphical methods. Scientific aim: The scientific aim of the article is to prove the established differences between business subjects that are the result of systematic influence (for example quality management system, subject of business, duration of action in the market). Findings: The research results have revealed the strengths of business subjects and revealed the areas which need to be improved. In the first place, they should become aware of the fact that the communication process necessarily forms the part of the complaints management and is well founded. The positive effect also has implementation of the existing ISO 9000 series of standards into business practice, which was reflected in a higher level of complaints management. Conclusions: Following the knowledge of communication process and its functioning plus awareness of communication obstacles, it is possible to improve the effectiveness and the result of communication and by that affect the overall result of claim procedure. Therefore, communication can be considered as very significant element in the process of complaints and claims handling.
Komunikace – významný prostředek nespokojenosti managementu
Keywords: business subjects; complaints management; communication process; customer